Process Investigation Perpetrator Action Criminal Terrorism In Indonesia - Rahmah Hayati Sinaga; Yasmirah Mandasari Saragih; Mhd Azhali Siregar; Azhar Hairi Putra; Mohammed Faiz Hadi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Terrorism is Wrong one crime Which outside normal Because has creating terror creates fear and that's scary has the impression of being cruel to groups or groups. The crime of terrorism has taken away rights basic para human victim Which No know anything about the origin , causes and the purpose of acts of terrorism. Because in in carrying out their actions perpetrators of this terrorism t is indiscriminate. This action is completely contrary to Article 3 Universal Declaration of Human Rights (UDHR) or Universal Declaration of Human Rights (UDHR) Which sounds